If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = -2 + -1j Solving 1 = -2 + -1j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add 'j' to each side of the equation. 1 + j = -2 + -1j + j Combine like terms: -1j + j = 0 1 + j = -2 + 0 1 + j = -2 Add '-1' to each side of the equation. 1 + -1 + j = -2 + -1 Combine like terms: 1 + -1 = 0 0 + j = -2 + -1 j = -2 + -1 Combine like terms: -2 + -1 = -3 j = -3 Simplifying j = -3
| j-2=4 | | 5x^2+48x+36/10x^2+48x | | x^3+6x^2= | | 27.4=p-28 | | -2(2x-3)=3(5-4x) | | u-90=-82 | | 3c+4d+3d= | | 2.4(x+3.2)=1.4x+x+4.5 | | 3+(-4/7) | | x/3=x-2/6 | | -2/7*-2 | | -4x-6=15-12x | | 29=28-b | | 21+26m=35+19 | | x+8(-1)=-3 | | z-6=2 | | 2y+6=3x | | -7+x+1/2-15 | | y=0.063x-1.26 | | -3(5-x)=18 | | 11=9-v | | 5-9x=43-23x | | 3/4x-9=42 | | 1=-1-g | | (4x-25)=(2x-5) | | j-2=2 | | -9p-4(4-4p)=4(p-4)-24 | | 180=x*96.04 | | 5n-11=3n+5 | | 15=11-n | | -7(x+1)-13=30+6 | | y=13-8x |